2018
DOI: 10.1002/biof.1456
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 knock‐down promoting tumor cells viability and arrest pro‐apoptotic proteins via Stat3/NFκB in HepG2 cells

Abstract: Background/Aim: High mobility group box 1 protein (HMGB1) is functionally dynamic and pleiotropic molecule, it has the potential to promote both cell survival and death by regulating multiple signaling pathways, including inflammation and apoptosis. This study aimed at investigating the role of silencing HMGB1 on tumor cells apoptosis and pro-inflammatory proteins expression in hepatocellular HepG2 cancer cells. Methods: HepG2 cells was transfected with si-RNA HMGB1, and the effect on pro-apoptotic proteins ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Mounting evidence shows that HMGB1 can promote the malignant progression of different types of cancer through the NF-κB signalling pathway 15 - 17 . To explore whether HMGB1 plays a pivotal role in the regulation of EPHB4 and NF-κB signalling pathways in OSCC cells, western blot analysis was performed and showed that HMGB1 expression was down-regulated following EPHB4 suppression in SCC9 and UM1 cells and vice versa (Figure 5 E, 5F).…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence shows that HMGB1 can promote the malignant progression of different types of cancer through the NF-κB signalling pathway 15 - 17 . To explore whether HMGB1 plays a pivotal role in the regulation of EPHB4 and NF-κB signalling pathways in OSCC cells, western blot analysis was performed and showed that HMGB1 expression was down-regulated following EPHB4 suppression in SCC9 and UM1 cells and vice versa (Figure 5 E, 5F).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of STAT3 induces tumor cell proliferation by promoting cell‐cycle progression, enhances tumor cell survival by inhibiting apoptosis, and accelerates tumor invasion and migration by promoting epithelial‐mesenchymal transition (EMT) . In addition, STAT3 is reported to mediate cancer stem cell–like property by enhancing anoikis resistance, which is related to chemoresistance and poor prognosis . However, in HCC, little is known about the clinical significance of STAT3 function, and the precise mechanisms of its activation are still unclear.…”
mentioning
confidence: 99%
“…Because STAT3 is strongly related to inflammatory responses, its activation is induced by inflammatory cytokines and chemokines. In addition, activation of nuclear factor kappa B (NF‐κB), a potent inflammation‐related transcriptional factor, is known to accelerate STAT3 activation . In contrast, gene associated with retinoid‐interferon‐induced mortality 19 (GRIM19) is known to be a strong suppressor for STAT3 activation .…”
mentioning
confidence: 99%
See 2 more Smart Citations